Covet - Wolff, Tracy (2021)
I may have reached my breaking point. As if trying to graduate from a school for supernaturals isn't stressful enough, my relationship status has gone from complicated to a straight-up dumpster fire. Oh, and the Bloodletter has decided to drop a bomb of epic proportions on us all... Then again, when has anything at Katmere Academy not been intense? And the hits just keep coming. Jaxon's turned colder than an Alaskan winter. The Circle is splintered over my upcoming coronation. As if things couldn't get worse, now there's an arrest warrant for Hudson's and my supposed crimes--which apparently means a lifetime prison sentence with a deadly unbreakable curse. Choices will have to be made...and I fear not everyone will survive.
Sequel to: Crush.
Keywords: Vampires -- Juvenile fiction; Boarding schools -- Juvenile fiction; Teenagers -- Juvenile fiction; Good and evil -- Fiction; Boarding school students -- Fiction; Young adult fiction; Vampire fiction; Romance fiction; Paranormal fiction; School fiction; Novels